Abdominal compartment syndrome and mixed germ cell tumor: A case of multidisciplinary management and long-term disease-free survival - Natalie L. Ayoub; Rebecca Shin; Patrick Peñalosa; Marisa Liu; Lourdes Swentek; Jill Tseng (Gynecologic Oncology Reports)
Introduction: Abdominal compartment syndrome is a life-threatening condition caused by elevated intra-abdominal pressure. The most common causes of abdominal compartment syndrome include trauma, burns, and acute pancreatitis. Gynecologic etiologies rarely cause abdominal compartment syndrome, especially in the setting of tumor rupture or hemorrhage. We present an unusual presentation of abdominal compartment syndrome and associated posterior reversible encephalopathy syndrome (PRES) caused by a ruptured mixed germ cell tumor. Case Description: A 26-year-old female presented with abdominal pain, a large abdominopelvic mass measuring 15 × 22 × 27 cm and elevated tumor markers concerning for an ovarian germ cell tumor. During admission, the patient developed hemodynamic instability, PRES, acute kidney injury, and elevated intravesical pressure consistent with abdominal compartment syndrome. She underwent emergent surgical decompression with an exploratory laparotomy, tumor debulking, and unilateral oophorectomy. Final pathology confirmed stage IIIC1 mixed germ cell tumor. Postoperatively, she received six cycles of bleomycin, etoposide, and cisplatin therapy (BEP). She has remained disease-free since completion of treatment, now totaling three years. Discussion: This case demonstrates a rare presentation of a newly diagnosed ovarian malignancy and highlights the rapid decompensation of patients with abdominal compartment syndrome. Acute surgical intervention is critical for survival, and prioritization of patient stability over extensive debulking reflects the nuanced intraoperative decision-making that is required in high-risk scenarios. Conclusion: Early recognition and coordination of care are important in effectively managing compartment syndrome in patients with gynecologic malignancies. Although uncommon, abdominal compartment syndrome should remain in the differential diagnosis for patients with acute decompensation and a large abdominopelvic mass.